“Together We’re Strong:” Cross-Cultural Solidarity in Angie Cruz’s Dominicana - Daniel Arbino (Latin American Literary Review, 2022)
In this article, I examine how Dominican American author Angie Cruz’s novel Dominicana (2019) uses the bildungsroman genre to point to cross-cultural solidarity, or different communities working in tandem, to contest hegemonic discourse. Cruz’s take on a bildungsroman has an interesting inflection that juxtaposes learning and unlearning in two different societies (Dominican and American) where lessons do not inform each other. Because Cruz's main protagonist Ana’s sense of Self develops alongside her civic engagement, I argue that it is useful to think of Dominicana as a feminist bildungsroman. Along with her brother-in-law César, Ana searches for change through relationality and intercultural empathy as vehicles toward larger community engagement that shares a common plight. Due to her peripheral positionality as an undocumented, non-English-speaking Person of Color in 1960s New York, she finds a location of identity within an alternative community of African American and white protestors, whose intersection is of class and political beliefs. My goal is not to overlook or minimize differences between groups, differences that have, at times, been contentious, but rather to emphasize that Cruz’s sense of belonging is guided by increased engagement in alternative communities that share in her alienation. Utilizing a theoretical lens grounded in the works of Jill Toliver Richardson, Rita Felski, and Amy Cummins and Myra Infante-Sheridan, I conclude that for Cruz, intercultural empathy and alternative communities are viable paths toward resisting the American national community that presents itself as an unattainable model of assimilation.